Medication Adherence and Drug Attitude Amongst Male Patients with the Methamphetamine-Induced Psychotic Disorder After Discharge: A Three Months Follow Up Study. Issue 1 (1st January 2022) - Asadi, Marzieh; Rashedi, Vahid; Khademoreza, Nooshin; Seddigh, Ruohollah; Keshavarz-Akhlaghi, Amir-Abbas; Ahmadkhaniha, Hamidreza; Rezvaniardestani, Seied-Mohamadhosein; Lotfi, Ali; Shalbafan, Mohammadreza
ABSTRACT: Medication adherence and attitudes toward psychiatric medication affect treatment outcome. The objective of this study was to evaluate the effect and interaction of psychotic symptoms, sociodemographic factors, and attitudes concerning medication use with a three-month follow-up among methamphetamine-induced psychotic male patients. In this prospective, descriptive study, 42 male patients diagnosed with a methamphetamine-induced psychotic disorder were selected on the last day of their admission period in Iran Psychiatry Hospital, Tehran, Iran. Each patient was evaluated using the Persian version of the Drug Attitude Inventory (DAI-10), Medication Possession Ratio (MPR), Positive and Negative Syndrome Scale (PANSS), as well as a sociodemographic questionnaire immediately, one month and three months after discharge. There was a significant difference in MPR between the first and third months. Moreover, the frequency of patients with a positive attitude toward their medications increased over time. Indeed, all participants stated a positive attitude at the last follow-up based on the DAI-10 cutoff. Based on our findings, medication adherence of male patients with methamphetamine-induced psychotic disorder should be an essential aspect of treatment after discharge from psychiatry inpatient wards, more specifically, through the first months.